2015
DOI: 10.1007/s13280-015-0709-x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping species distributions: A comparison of skilled naturalist and lay citizen science recording

Abstract: To assess the ability of traditional biological recording schemes and lay citizen science approaches to gather data on species distributions and changes therein, we examined bumblebee records from the UK’s national repository (National Biodiversity Network) and from BeeWatch. The two recording approaches revealed similar relative abundances of bumblebee species but different geographical distributions. For the widespread common carder (Bombus pascuorum), traditional recording scheme data were patchy, both spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 30 publications
1
44
0
Order By: Relevance
“…Although most insect taxa require physical specimens to be collected in order for identifications to be made (Kremen et al 2011), Bumble bees can sometimes be identified to species by photos (Lye et al 2012;Richardson et al 2019;van der Wal et al 2015;Beckham and Atkinson 2017; The Xerces Society for Invertebrate Conservation, Wildlife Preservation Canada, York University, et al 2017). For example, 75% of the Bumble bee observations submitted to the iNaturalist Vermont site were identified to species through photos (Mcfarland et al 2016), and, as of January 31, 2018, 86% of all Bumble bee observations that had been submitted to Bumble Bee Watch and reviewed by an expert were identified to species (those records that were assigned a tentative identification were considered to not be identified to species, and both pending and invalid submissions (those that were not actually Bumble bees) were excluded from this analysis) (The Xerces Society for Invertebrate Conservation, Wildlife Preservation Canada, York University, et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most insect taxa require physical specimens to be collected in order for identifications to be made (Kremen et al 2011), Bumble bees can sometimes be identified to species by photos (Lye et al 2012;Richardson et al 2019;van der Wal et al 2015;Beckham and Atkinson 2017; The Xerces Society for Invertebrate Conservation, Wildlife Preservation Canada, York University, et al 2017). For example, 75% of the Bumble bee observations submitted to the iNaturalist Vermont site were identified to species through photos (Mcfarland et al 2016), and, as of January 31, 2018, 86% of all Bumble bee observations that had been submitted to Bumble Bee Watch and reviewed by an expert were identified to species (those records that were assigned a tentative identification were considered to not be identified to species, and both pending and invalid submissions (those that were not actually Bumble bees) were excluded from this analysis) (The Xerces Society for Invertebrate Conservation, Wildlife Preservation Canada, York University, et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work in the UK with the BeeWatch program (Lye et al 2012;van der Wal et al 2015), the Texas Bumblebees Facebook page, and the iNaturalist Bees and Wasps of Texas project (Beckham and Atkinson 2017) suggests that citizen science projects based on photo submissions of bees can capture data complementary to that collected by experts and assist in learning more about, and tracking changes to, species over time. Bumble Bee Watch is a web-based citizen science program where participants photograph Bumble bees anywhere in North America, upload the photos and relevant site information to a website or through a hand held device, and work through an interactive identification key to arrive at a species name, which experts then verify (The Xerces Society for Invertebrate Conservation, Wildlife Preservation Canada, York University, et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Citizen science has proven useful in examinations of pollinator distributions and declines (Matteson et al 2012;Moskowitz and Haramaty 2013;Stafford et al 2010), responses to climate change (Breed et al 2012), population genetics (Harpur et al 2015), detection of exotic species (Ashcroft et al 2012;Wal et al 2015), nesting and hive properties (Graham et al 2014;Lye et al 2012;Sponsler and Johnson 2015), pesticide impacts (Muratet and Fontaine 2015), responses to habitat and landscape features (Bates et al 2014;Everaars et al 2011;Kremen et al 2011), migrations (Davis et al 2012Howard and Davis 2015;2009), overwintering (Howard et al 2010), disease dynamics (Satterfield et al 2015), and larval survivorship (Nail et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…I n this study, citizen science programs have flourished in ecology, with many benefits such as an extension of spatial and temporal scales (including data collection on private areas such as gardens), time and cost reduction, and reconnection of people with nature leading to an increasing public awareness about environmental issues (Bonney et al 2009;Devictor et al 2010;Dickinson et al 2010;Birkin and Goulson 2015;van der Wal et al 2015).…”
Section: Bee Sampling and Identificationmentioning
confidence: 99%